Results from a Patient-Based Health Education Intervention in Reducing Antibiotic Use for Acute Upper Respiratory Tract Infections in the Private Sector Primary Care Setting in Singapore - Lee, Magdalene Hui Min (AMER SOC MICROBIOLOGY, 2019)
10.1128/AAC.02257-16